15 Dissociation of conceptual knowledge of social behaviour and the knowledge of its consequences in frontotemporal lobar degeneration. Issue 8 (13th July 2017) - Zahn, Roland; Green, Sophie; Beaumont, Helen; Burns, Alistair; Moll, Jorge; Caine, Diana; Ralph, Matthew Lambon
Abstract : Objective: The objective assessment of socially inappropriate behaviour in patients with frontotemporal lobar degeneration (FTLD) is difficult and hampered by its elusive cognitive basis. Neuropsychological tests of social cognition such as complex theory- of-mind tasks are unlikely to be helpful for early differential diagnosis in the future, because patients with non-neurological disorders show impairments on these tasks and they are confounded with general executive abilities. Here, we used a newly developed test of the knowledge of the consequences of social behaviour to investigate whether this can be impaired in patients with FTLD relative to a previously developed test of social conceptual knowledge. Method: We included 19 consecutive patients with features of bvFTD or SD. Based on their background neuropsychological tests and neuroimaging features, we classified patients into those with primary neurodegeneration of the anterior temporal lobes (ATL group, n=12), those with primary neurodegeneration outside the ATL (non-ATL group, n=5) and those with global impairment or atrophy (n=2). Results: As predicted, we found conceptual knowledge of social behaviour to be impaired in the primary ATL group whilst knowledge of its long-term consequences was relatively preserved compared with the non-ATL group. In contrast, the non-ATL group showed impaired performance on the task probing knowledge of long-term consequences with relatively better conceptual social knowledge compared with the ATL group. Conclusions: This shows that conceptual and sequential knowledge of social behaviour are dissociable and are likely to independently contribute to socially inappropriate behaviour. Short versions of these social conceptual and sequential knowledge tests are therefore promising tools for improvement of differential diagnosis when added to standard test batteries.